Types of Musical Interaction in the Family and Everyday Context: Bruna's musical relationship with her parents - Lerma Arregocés, Daniela (Epistemus. Journal of Studies in Music, Cognition & Culture, 2023)
In the field of Early Childhood Education, musical communication between adults and children has been recurrently studied. Most research on this topic has prioritized the adult perspective when observing the interaction with the infant, which has led to an incomplete characterization of this phenomenon. The present qualitative and emergent study has adopted the audio recording technology LENA® (Language ENvironment Analysis) to document real situations from the daily life of five families with at least one child, and to know the type of parental-child participation in everyday musical and vocal interactions, primarily the contextual, musical, and communicative elements that compose them. This article presents the results of one of the participating families through descriptions of their musical encounters that exemplify six types of interactions (dialogue, synchrony, solo, fill the gap, imitation, and contrast) detected with an analysis tool designed and validated for this research. These descriptions are accompanied by graphic representations that visualize the interventions of each participant and give a deeper understanding of the individual behaviors of both adult and infant within the same phenomenon that is participatory and shared.